DIRECT AND INDIRECT SOMATIC EMBRYOGENESIS ON ARABICA COFFEE (Coffea arabica) - Meynarti Sari Dewi Ibrahim; Rr. Sri Hartati; Rubiyo Rubiyo; Agus Purwito; Sudarsono Sudarsono (Indonesian Journal of Agricultural Science, 2013)
Propagation of Coffea arabica L. through direct and indirect somatic embryogenesis technique is promising for producing large number of coffee seedlings. The objectives of the research were to evaluate methods for direct and indirect somatic embryo-genesis induction of C. arabica var. Kartika. The explants were the youngest fully expanded leaves of arabica coffee. The evalu-ated medium was modified Murashige and Skoog (MS) medium supplemented with a combination of 2.26 µM 2,4-D + 4.54 or 9.08 µM thidiazuron; 4.52 µM 2,4-D + 4.54 or 9.08 µM thidiazuron; or 9.04 µM 2,4-D + 9.08 µM thidiazuron. Both calli (100 mg) and pre-embryos developed from the edge of leaf explants were subcultured into regeneration medium (half strength MS with modified vitamin, supplemented with kinetine 9.30 µM and adenine sulfate 40 mg L-1). The results showed coffee leaf explant cultured on medium containing 2.26 µM 2,4-D + 4.54 or 9.08 µM thidiazuron to induce direct somatic embriogenesis from explant, while that of 4.52 or 9.04 µM 2,4-D + 9.08 µM thidiazuron to induced indirect somatic embrio-genesis. The medium for calli induction from coffee by explants was medium supplemented with 4.52 or 9.04 µM 2,4-D in combination with 9.08 µM thidiazuron. On the other hand, the best medium for activation of induction of somatic embryos was MS medium supplemented with 9.04 µM 2,4-D + 9.08 µM thidiazuron. Based on this results, the first step for developing micropropagation for coffee has been resolved. The subsequent studies will be directed to evaluate agronomic performance of the derived planting materials.